International Advances in Foot and Ankle Surgery - Saxena, Amol.; SpringerLink (Online service) (London : Springer London, 2012)
A comprehensive textbook of some of the most common and difficult to deal with pathologies. The first truly international, multidisciplinary manual of foot and ankle surgery by the specialty$1 (Bs leaders and most experienced surgeons. The management of various conditions in the foot and ankle will be approached by authors in different parts of the world. Authors will be invited to provide radiographs, diagrams, and intra-operative pictures to illustrate the procedures described. Current up to date trends and techniques using a scientific approach including evidence based guidelines where applicable. The reader will be exposed to a step-by-step approach to each procedure presented. No outcome research has been performed in this area, and the book may serve as a reference in this respect.s
Distal First Metatarsal Osteotomy -- Hallux Valgus: Proximal First Metatarsal Osteotomies -- The Lapidus Procedure -- Hallux Rigidus: The Valenti Arthroplasty -- Hallux Rigidus: Distal First Metatarsal Osteotomy/Hohmann Procedure -- Hallux Rigidus: Proximal Phalangeal Osteotomy/Enclavement Procedure -- Arthrodesis of the First Metatarsalphalangeal Joint -- Hallux Rigidus: First Metatarsal Head Resurfacing -- Revision Hallux Valgus Surgery -- Second Metatarsophalangeal Joint Arthropathy -- Tailor$1 (Bs Bunionectomy -- Surgical Treatment of Hammer Toe, Claw Toe, and Mallet Toe Deformity -- Current Techniques of Toenail Surgery -- Forefoot Trauma -- Fractures of the Calcaneus -- Fractures of the Talus -- Percutaneous Plating of Ankle Fractures -- Ankle Instability -- Insertional and Midsubstance Achilles Tendinopathy -- Peroneal Tendinopathy -- First Metatarsophalangeal Joint Sesamoidopathy -- Turf Toe Injuries -- Lisfranc$1 (Bs and Midfoot Injuries -- Stress Fractures of the Foot and Ankle in Athlete -- Plantar Fasciitis -- Osteochondral Lesions of the Talus -- Os Trigonum Injuries -- Syndesmosis Injuries -- Acute Repair of Ruptured Foot and Ankle Tendons in Athletic Patients -- Chronic Compartment Syndrome of Leg and Foot -- Pedal Amputations in Diabetes -- Charcot Foot and Ankle Disease -- Rheumatoid Foot Reconstruction -- The Pediatric Foot -- Surgical Treatment of Flexible Flatfoot in Adolescents with Bioabsorbable Implant -- Acquired Adult Flatfoot Deformity -- Cavus Foot -- Advances in Anterior Ankle and Subtalar Arthroscopy -- Posterior Ankle Arthroscopy and Endoscopy -- Endoscopic Gastrocnemius Recession -- Use of External Fixation in the Lower Extremity -- Intramedullary Nail Fixation for Tibiotalocalcaneal Arthrodesis -- Total Ankle Arthroplasty: The U.S. Experience -- Tumors and Tumor-Like Lesions of the Foot and Ankle: Diagnosis and Treatment -- Post-Operative Physical Therapy for Foot and Ankle Surgery.s
Keywords: Medicine; Orthopedics; Orthopedic surgery; Rehabilitation; Sports medicine; Endoscopic surgery; Medicine & Public Health; Surgical Orthopedics; Sports Medicine; Orthopedics; Conservative Orthopedics; Rehabilitation Medicine; Minimally Invasive Surgery